Profile of users intoxicated by drugs of abuse and association with death - Lúcia Margarete dos Reis; Aroldo Gavioli; Flavia Antunes; Michele Cristina Santos Silvino; Natalina Maria da Rosa; Magda Lúcia Félix de Oliveira (Rev Rene)
Objective: to characterize the profile of users intoxicated by drugs of abuse reported to a center of information and toxicological assistance  and related this to the occurrence of deaths.Methods: study of case series reported in the 2010-2011 biennium after active case finding. Data were obtained from epidemiological records filed in the center and submitted to univariate analysis, with chi-squared test and Fischer test. Results: three hundred and thirty nine cases were found, most were men (87.3%), with basic education (61.0%) and elderly (37.2%). Alcohol use (83.8%) and chronic intoxications (89.9%) were predominant. Clinical complications were present in most medical diagnoses (63.4%). However, mortality was higher in the event deferral by cold and fire weapons. Conclusion: the consumption of drugs of abuse influences morbidity and mortality, particularly in men aged at 60 years or above and with low level of education.